Evaluation of Changes in Semen Parameters Following Varicocelectomy in Varicocele Patients - Satish Parihar; Gurbir Singh; Ab Hamid Wani; Rahul Singh; Mithlesh Wanchoo (Dr. Annil Mahajan, 2023)
Background: Varicocele is an abnormal degree of venous dilatation in pampiniform plexus of testis. The male infertility causes are multifactorial and varicocele occupies a significant position with a prevalence of 19-41% in cases of primary infertility and 45-81% among cases of secondary infertility. Methods: The study was conducted in the Department of Surgery, Government Medical College, Jammu. A detailed history was taken from all the patients followed by physical examination. Scrotal ultrasonography was carried out for detecting the varicocele and further grading. A total of 42 male patients were included. Results: Maximum patients were in the age group of 21-40years of age. Most of the patients presented with grade IV varicocele with 47.6%. The mean pre-op volume was 2.46±0.949ml and the mean post-op volume was 2.90±0.753ml. The mean pre-op motility was 51.60±19.313% and the mean post-op motility was 58.40±16.839%. The mean pre-op concentration was 41.80 ±24.856million per ml and the mean postop concentration was 43.00 ±22.128million per ml. Conclusion: There is definite improvement in sperm parameters with statistically significant increase in semen volume, sperm motility and sperm concentration following varicocele repair. The grade of varicocele is also essential as lower grades of varicocele shows higher rates of improvement in semen parameters post-varicocelectomy.